The Enhancement of Skills Through Eco-Printing Training With Pounding Technique Among PKK Groups in Bangunjiwo Village, Bantul - Kholifah, Nur; Triyanto, Triyanto; Eka Putri, Gina; Fitrihana, Noor; Istanti, Hanifah Nur; Mafiroh, Desfina; Ningrum, Vaisa Ayu (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The objective of this Community Service Program (PkM) is to enhance the skills in creating ecoprinting products using the pounding technique for small business owners or novice entrepreneurs, specifically the PKK women’s group in Bangunjiwo Village, Bantul. This program involves twenty participants and a ten-member organizing committee from UNY's Vocational Faculty's Fashion Design Study Program, including five lecturers and five students. The stages of the PkM activities include needs analysis, preparation, implementation, and evaluation, conducted from March to June 2023. The outcomes of the PkM activities indicate that the feedback from the ecoprinting instructors using the pounding technique averaged 4.2 out of 5.0, categorized as good. The increase in participants' knowledge was obtained with an average N-gain value of 0.56 (56.27%) which was categorized as quite effective. The creativity of the products produced had an average score of 84.5 out of 100. Specific skills that need to be considered to produce high-quality products include recognizing the characteristics and experimental treatment of certain leaves, the type of surface of the pounding tool, the position, and accuracy on the stem and vein ends of the leaves, fabric dyeing strategies, and the patterns produced, as well as drying the fabric naturally or by air-drying. Another important aspect is the creativity in arranging leaves to achieve high artistic value and meaningful aesthetics. The quality of ecoprinting products using the pounding technique requires repeated training and experimentation to produce varied colors from leaf pigments and to select leaves with unique and interesting patterns.